Psycho-emotional personality traits affecting therapy compliance in patients with pain and painless forms of coronary heart disease - L. A. Biryukova; T. N. Panova; L. P. Velikanova (Российский кардиологический журнал, 2008)
High levels of medico-social therapy compliance were observed in coronary heart disease patients with adaptive psychoemotional reactivity types. Decreased compliance was associated with psycho- emotional disadaptation, typical for patients with pain type of myocardial ischemia.